United Kingdom : Financial Sector Assessment Program-Select Issues in Financial Safety Net Arrangements and Financial Crisis Preparedness. (IMF Staff Country Reports; Country Report, 2022)
The United Kingdom (U.K.) bank resolution and financial crisis readiness arrangements are sound but with opportunities for continued and accelerated enhancements. The U.K. authorities' individual and collective crisis readiness-including with other major jurisdictions-continues to improve. Mid-2022, all major U.K. banks and the authorities will issue the first public statements about these banks' resolvability. This is supported by a comprehensive special resolution regime (SRR) and resolvability assessment framework (RAF) for banks. Yet, there is space-and a need-to further enhance the SRR, including its application to central counterparties (CCPs), and to introduce one for insurance companies. Furthermore, elements of the deposit insurance system and firm-specific resolution decision-making should be strengthened, and implementation and reputation risk addressed.